2000
DOI: 10.1016/s0008-6363(00)00088-2
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant effects of a novel iron chelator salicylaldehyde isonicotinoyl hydrazone in the prevention of H2O2 injury in adult cardiomyocytes

Abstract: The data indicate that SIH provides a very powerful and very fast protection against the oxidative stress exerted by H(2)O(2) presumably via the iron-mediated Fenton reaction producing hydroxyl radical (OH), whereas the protective effect of DFO is hindred by its very slow and rather limited intracellular entry, and the protection that MIA exerts via the inhibition of Na(+)/H(+) exchange against H(2)O(2) much less effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 25 publications
6
49
0
Order By: Relevance
“…8,11,12 In our study, iron-overloaded mice had increased mortality and displayed bradycardia. The effects of iron overload on mortality are consistent with observations showing that free radical-mediated lipid peroxidation alters cardiomyocyte electrophysiology 42,50 and Ca 2ϩ handling 20,43 and blockade of electrical conduction and sudden death in iron-overloaded guinea pigs. 51 Our strategy was to increase myocardial taurine levels to protect the cardiovascular system and prevent iron overloadinduced cardiovascular dysfunction, even though myocardial taurine levels were not affected by iron overload.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…8,11,12 In our study, iron-overloaded mice had increased mortality and displayed bradycardia. The effects of iron overload on mortality are consistent with observations showing that free radical-mediated lipid peroxidation alters cardiomyocyte electrophysiology 42,50 and Ca 2ϩ handling 20,43 and blockade of electrical conduction and sudden death in iron-overloaded guinea pigs. 51 Our strategy was to increase myocardial taurine levels to protect the cardiovascular system and prevent iron overloadinduced cardiovascular dysfunction, even though myocardial taurine levels were not affected by iron overload.…”
Section: Discussionsupporting
confidence: 87%
“…These aldehyde products are generated by free radical-induced lipid peroxidation and participate in cytotoxic reactions, leading to cellular dysfunction 48,49 including altered excitationcontraction coupling and electrophysiology and defective contractile function. 20,42,43,50 Indeed, a distinct feature of iron-overload cardiomyopathy in humans is the increased susceptibility to various arrhythmias, including bradyarrhythmias and cardiac death. 8,11,12 In our study, iron-overloaded mice had increased mortality and displayed bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“…A concentration of 0.25 mmol/l consistently produced recordable negative inotropic effects, and 0.4 mmol/l produced marked, statistically significant, negative inotropism. These concentrations are also consistent with recent studies done by others (3,6,8,14) in the rodent myocardium. After several minutes, concentrations Ͼ0.4 mmol/l regularly produced contracture, cardiac arrest, and ventricular fibrillation.…”
Section: Hydrogen Peroxide and Acetaminophensupporting
confidence: 93%
“…Another purpose was to investigate several antioxidant mechanisms that might help explain the cardioprotective properties of acetaminophen, e.g., does acetaminophen attenuate the negative inotropic actions of exogenously administered hydrogen peroxide? The latter objective seemed important because it is well known that hydrogen peroxide releases hydroxyl radical via the Fenton reaction (2,14), and it has already been shown that acetaminophen attenuates the production of hydroxyl radical in the postischemic-reperfused myocardium (21).…”
mentioning
confidence: 99%
“…Alternatively, iron chelation was achieved using salicylaldehyde isonicotinoyl hydrazone (SIH; 100 M) (27) (a kind gift from Dr. P. Ponka (McGill University, Montreal, Quebec, Canada)). SIH was prepared and kept at 4°C until used, as described elsewhere (27). Hemin (Frontier Scientific, Logan, UT) was dissolved in 0.2 N NaOH, neutralized to pH of 7.4 using 1 N HCl, and stored at Ϫ20°C until used.…”
Section: Reagentsmentioning
confidence: 99%